LITERASI DIGITAL PETANI DI DESA SEKITAR KAWASAN INDUSTRI: STUDI KASUS DI KAWASAN INDUSTRI BATANG, JAWA TENGAH - Fadhilah, Muhammad Luthfie; Fauziah, Irma; Rahmaningtyas, Avivah (Journal of Agribusiness, Social and Economic, 2025)
The rapid development of industrial areas in Indonesia presents unique challenges for the community, particularly in adapting to technology and information. In this context, digital literacy is a crucial aspect that determines the ability of farmers to maintain and develop their agricultural practices amidst the flow of modernization and digitalization that accompanies the growth of industrial areas. The objectives of this study are: 1) to analyze the factors that determine the digital literacy of farmers around the Batang Industrial Park area, and 2) to examine the differences in digital literacy levels between farmers located in areas directly adjacent to the industrial area and those located in areas that are not directly adjacent. The research method used a survey. The analysis used multiple linear regression analysis and the Wilcoxon-Mann-Whitney difference test. The study's results indicate that age and education significantly influence farmers' digital literacy level. The older the farmer, the lower the digital literacy. Meanwhile, about education, the higher the level of education, the higher the level of digital literacy of farmers. Furthermore, there are differences in digital literacy levels between farmers located in areas directly adjacent to the Batang Industrial Park area and in areas not directly adjacent. Stakeholders need to collaborate to improve digital farmer literacy, such as by providing access to digital devices and regular training on the use of digital agricultural technology, so that farmers can keep up with current developments and improve the efficiency of their businesses.